Determinants Of Physical Store's Customer Satisfaction Among University Students - Panirchelvam, Dinesh; Abdullah, Norida; Mohammad Rawi, Ali Hafizar; Mohd Noor, Ahmad Ridzwan; Al-Shami, Samer Ali Hussein (Allied Business Academies, 2021)
Physical stores in Malaysia has witnessed positive growth due to various developments in the retail industry. However, physical stores are facing strong market competitions from online stores as a result/impact of industrial revolution 4.0. This is because there is still a lack of study to explain how customer satisfaction can be develop by physical stores in sustaining competitive advantage against online stores. This study identifies the determinants of physical store’s customer satisfaction among university students. Specifically, factors such as price fairness, customer service and marketing strategy are taken into consideration in order to study their effects on physical store’s customer satisfaction. Quantitative research method was used through survey questionnaire. The sampling method used in this study is convenience sampling. University students N=300 were selected from a public university. A standard questionnaire was used to access respondent’s information and data. The questionnaire’s data were analysed by using SPSS software. It was found that price fairness, customer service and marketing strategy are the determinants of physical store’s customer satisfaction among university students, (p<0.000). This study is helpful for physical store managements to increase customer satisfaction and enhance competitive advantage against online stores.